To the synthesis of the initial algorithms for control and diagnostic control of discrete automata based on programmable logic controllers - Ivanushkin, Viktor Andreevich; Isakov, Dmitry Viktorovich; Volkov, Mikhail Anatolievich (AIP conference proceedings, 2022)
The article deals with a systematic approach to the design of software and logic control systems and the use of formal methods for the synthesis of process control algorithms and functional diagnostics algorithms, which makes it possible to create logical control devices for cyclic processes with lower costs for the design, debugging and operation of equipment. The addition of control algorithms to diagnostic algorithms allows you to quickly determine the cause and location of the fault, reduce downtime of technological equipment and thereby increase its productivity. The possibilities of different programming languages of logic controllers in the implementation of tasks of functional diagnostics and control of command execution are compared. The differences and advantages of the methodology of joint synthesis of the initial control algorithms and diagnostic control of discrete automata in comparison with the traditional approach in the separate synthesis of control algorithms and diagnostic control of the execution of operations by actuators are considered.